The study of the intestine-brain axis and its influence in neurodegenerative diseases - a literature review (Research, Society and Development, 2022)
The intestine plays a fundamental role in the relationship with the brain due to a bidirectional communication between both that connects the central nervous system to the so-called enteric nervous system, these systems are kept connected by the vagus nerve. The intestine has bacteria, viruses, fungi and protozoa responsible for the health of the intestinal microbiota and also produce and release neurotransmitters, your mental and physical health is directly related to the type of food used to feed these living beings of the intestinal microbiota. The objective of this work was to discuss the possible relationship between the intestinal microbiota and neurodegenerative diseases. The present study is a literature review on the gut-brain axis and its influence on neurodegenerative diseases. Databases such as Google academic, PUBMED, SciELO, SCIELO, Oxford academic, ingentaconnect, Europe PMC, Nature journal, Brazilian Journal were used. Books, journals or scientific journals and scientific research sites on the internet were reviewed and criteria used as the title of the article. Based on the 40 studies analyzed in the last eleven years , it was found that the intestinal microbiota has an influence on the gut-brain relationship, the association that exists between neurodegenerative diseases and the imbalance of the intestinal microbiota; and, as an aid in the management of these diseases, nutritional strategies.